(untitled) (American Journal of Islam and Society, 2009)
Over the last two to three decades, a number of factors have ensured that western Muslims and Islam have become socially and politically far more embedded and visible in western liberal democracies. For example, a large segment of new (post-1965) immigrant religious minority communities settling in western liberal democracies, including Canada, are of the Muslim faith. Moreover, an increasing number of educated, professional westernborn Muslims consider, unlike their immigrant parents, their countries of birth as their “home.” Furthermore, the politicization of Islam and the nature of the current state of international affairs, in which issues pertaining to Muslims and Islam often take central place, have highlighted the public prominence of Islam and its adherents in theWest. This situation has problematized and generated a number of debates relating to the philosophical, religious, cultural, political, and social underpinnings of western liberal societies vis-à-vis their Muslim community constituency. In addition, it has induced several profound identity-related questions pertaining to what it means to be “western” or “a westernMuslim” or, for some, a “Muslim” in theWest. One aspect of this overall dynamic is the question of the role and the function of faith-based Islamic schools operating in western liberal democracies, as their numbers have mushroomed over the last two decades ...